2016
DOI: 10.1038/srep36550
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community structure and function shift along a successional series of tidal flats in the Yellow River Delta

Abstract: Coastal ecosystems play significant ecological and economic roles but are threatened and facing decline. Microbes drive various biogeochemical processes in coastal ecosystems. Tidal flats are critical components of coastal ecosystems; however, the structure and function of microbial communities in tidal flats are poorly understood. Here we investigated the seasonal variations of bacterial communities along a tidal flat series (subtidal, intertidal and supratidal flats) and the factors affecting the variations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
46
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 61 publications
(115 reference statements)
10
46
1
1
Order By: Relevance
“…Compared with river or marine sediments, the intertidal wetland showed a unique pattern of bacterial diversity. The pattern is concordant with recent findings about bacterial communities in intertidal sediments . Bacteroidetes were positively correlated with salinity in wetland sediments and were the dominant group in sediments with higher salinity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared with river or marine sediments, the intertidal wetland showed a unique pattern of bacterial diversity. The pattern is concordant with recent findings about bacterial communities in intertidal sediments . Bacteroidetes were positively correlated with salinity in wetland sediments and were the dominant group in sediments with higher salinity.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a high variability in pH value, salinity, and concentrations of nutrients, which are main controlling factors of bacterial community structure, would be exhibited among different habitats. Previous studies mainly focused on either river to marine environments or intertidal wetland . Comparison of the bacterial diversity in sediments from freshwater, intertidal wetland, and marine was revealed for the first time in the Pearl River in south China , but the correlation between bacterial community structure and environmental factors is unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…We found that, at the phylum level, the saltpan bacterial community was dominated by Proteobacteria, with Bacteroidetes and Planctomycetes dominating the remaining fraction. This finding is in agreement with commonly found patterns in both salt marsh [39,40] and tidal flat habitats [41]. Of the sequences classified at the genus level, Pseudomonas dominated and pseudomonads, as well as Flavobacterium, have been reported in coastal beach sediment, along with other genera characterized by salt tolerance and facultative anaerobic metabolisms [42,43].…”
Section: Discussionsupporting
confidence: 91%
“… Culture‐independent techniques have captured how microbial community composition in insects varies largely in time and space‐in response to diet, geography, season, and developmental stage (Hu et al., ; Wilhelm et al., ; Chaplinska et al., ; Lv et al., ; Vacchini et al, ; Bascuñán et al., ). The relevance of these parameters might vary according to the microbial groups, with environmental factors being more important for bacteria and fungi than in shaping the viral communities (Nouri et al., ).…”
Section: Discussionmentioning
confidence: 99%